(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
A stability indicating RP-UPLC method was developed and validated for simultaneous estimation Ofloxacin and Ornidazole in tablet dosage form. The separation was achieved under optimized chromatographic condition on a Waters® C18 Acquity UPLC BEH (100 mm × 2.1 mm, 1.7μm) column with mobile phase consist of Water: Acetonitrile: Triethylamine in the ratio of 85: 15: 0.1 v/v. An isocratic elution at a flow rate of 0.2 ml/min at ambient oven temperature was carried out with PDA detection at 300 nm. The retention time for Ofloxacin and Ornidazole was 3.9 min and 6.4 min respectively. The degradation was observed under acidic, alkali, oxidative, photolytic and thermal conditions. The linearity was found to be in the concentration range of 50-150μg/ml for Ofloxacin and 125-375μg/ml for Ornidazole. The % recoveries at 50% were found to be 100.46% & 100.22% for Ofloxacin & Ornidazole respectively. The % recoveries at 100% were found to be 99.70% & 99.83% for Ofloxacin & Ornidazole respectively. The % recoveries at 150% were found to be 99.67% & 100.30% for Ofloxacin & Ornidazole respectively. The method was validated as per ICH guideline and the values were found to be within the limits. So, the proposed method was found to be simple, linear, accurate, precise, stability indicating, robust and specific.